2003
DOI: 10.1086/373920
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tidal Inflation Instability on the Mass and Dynamical Evolution of Extrasolar Planets with Ultrashort Periods

Abstract: We investigate the possibility of substantial inflation of short-period Jupiter-mass planets, as a result of their internal tidal dissipation associated with the synchronization and circularization of their orbits. We employ the simplest prescription based on an equilibrium model with a constant lag angle for all components of the tide. We show that 1) in the low-eccentricity limit, the synchronization of the planets' spin with their mean motion is established before tidal dissipation can significantly modify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
223
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(225 citation statements)
references
References 54 publications
2
223
0
Order By: Relevance
“…As originally proposed by Bodenheimer et al (2001) and Gu et al (2003) and later studied by many authors (e.g. Jackson et al 2008;Ibgui & Burrows 2009;Miller et al 2009), stellar tides provide a way to transfer gravitational energy from the planetary orbit into the planet and either slow its contraction, or even produce a size inflation.…”
Section: The Effect Of Tidesmentioning
confidence: 98%
“…As originally proposed by Bodenheimer et al (2001) and Gu et al (2003) and later studied by many authors (e.g. Jackson et al 2008;Ibgui & Burrows 2009;Miller et al 2009), stellar tides provide a way to transfer gravitational energy from the planetary orbit into the planet and either slow its contraction, or even produce a size inflation.…”
Section: The Effect Of Tidesmentioning
confidence: 98%
“…Following Bodenheimer et al (2001) and Gu et al (2003), attempts have been made to explain the observed large radius of some transiting close-in gas giant exoplanets -the so-called "Hot Jupiters" -by means of tidal heating (Jackson et al 2008;Miller et al 2009;). All these models, however, use tidal models truncated to a low (2nd) order in eccentricity, in spite of initial eccentricities, as determined from the tidal evolution calculations, which can be as large as e = 0.8!…”
Section: Introductionmentioning
confidence: 99%
“…Their relatively large mass and small semimajor axis imply tidal interactions with the host star that should lead in most cases to a slow spiral-in of the planet and to a transfer of angular momentum to the star (e.g. Barker & Ogilvie 2009;Jackson et al 2009;Mastumura et al 2010), the end result being the planet's disruption at its Roche limit (Gu et al 2003). The timescale of this final disruption depends mostly on the timescale of the migration mechanism, the tidal dissipation efficiency of both bodies, and the efficiency of angular momentum losses from the system due to magnetic braking.…”
Section: Introductionmentioning
confidence: 99%